Factors influencing utilisation of 'free-standing' and 'alongside' midwifery units for low-risk births in England: a mixed-methods study - Denis Walsh; Helen Spiby; Christine McCourt; Dawn Coleby; Celia Grigg; Simon Bishop; Miranda Scanlon; Lorraine Culley; Jane Wilkinson; Lynne Pacanowski; Jim Thornton (National Institute for Health Research, 2020)
Background: Midwifery-led units (MUs) are recommended for 'low-risk' births by the National Institute for Health and Care Excellence but according to the National Audit Office were not available in one-quarter of trusts in England in 2013 and, when available, were used by only a minority of the low-risk women for whom they should be suitable. This study explores why. Objectives: To map the provision of MUs in England and explore barriers to and facilitators of their development and use; and to ascertain stakeholder views of interventions to address these barriers and facilitators. Design: Mixed methods - first, MU access and utilisation across England was mapped; second, local media coverage of the closure of free-standing midwifery units (FMUs) were analysed; third, case studies were undertaken in six sites to explore the barriers and facilitators that have an impact on the development of MUs; and, fourth, by convening a stakeholder workshop, interventions to address the barriers and facilitators were discussed. Setting: English NHS maternity services. Participants: All trusts with maternity services. Interventions: Establishing MUs. Main outcome measures: Numbers and types of MUs and utilisation of MUs. Results: Births in MUs across England have nearly tripled since 2011, to 15% of all births. However, this increase has occurred almost exclusively in alongside units, numbers of which have doubled. Births in FMUs have stayed the same and these units are more susceptible to closure. One-quarter of trusts in England have no MUs; in those that do, nearly all MUs are underutilised. The study findings indicate that most trust managers, senior midwifery managers and obstetricians do not regard their MU provision as being as important as their obstetric-led unit provision and therefore it does not get embedded as an equal and parallel component in the trust's overall maternity package of care. The analysis illuminates how provision and utilisation are influenced by a complex range of factors, including the medicalisation of childbirth, financial constraints and institutional norms protecting the status quo. Limitations: When undertaking the case studies, we were unable to achieve representativeness across social class in the women's focus groups and struggled to recruit finance directors for individual interviews. This may affect the transferability of our findings. Conclusions: Although there has been an increase in the numbers and utilisation of MUs since 2011, significant obstacles remain to MUs reaching their full potential, especially FMUs. This includes the capacity and willingness of providers to address women's information needs. If these remain unaddressed at commissioner and provider level, childbearing women's access to MUs will continue to be restricted. Future work: Work is needed on optimum approaches to improve decision-makers' understanding and use of clinical and economic evidence in service design. Increasing women's access to information about MUs requires further studies of professionals' understanding and communication of evidence. The role of FMUs in the context of rural populations needs further evaluation to take into account user and community impact. Funding: This project was funded by the National Institute for Health Research (NIHR) Health Services and Delivery Research programme and will be published in full in Health Services and Delivery Research; Vol. 8, No. 12. See the NIHR Journals Library website for further project information.